A CROSS-SECTIONAL STUDY ON THE IMPACT OF PHYSICAL ACTIVITY AND BODY MASS INDEX ON VITAMIN D LEVELS AMONG MEDICAL STUDENTS - BHAGYASHREE N; JANA , SHILPASREE; N, SMITHA; GOOTHY, SAI SAILESH KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Vitamin D has non-calcemic effects, like enhancing immunity and prevents premature aging. Vitamin D has antioxidant-like property, which is necessary for maintenance of body’s mineral balance. Severe vitamin D deficiency is associated with an increased risk of death from diseases such as cardiovascular conditions, diabetes, cancer, and infertility. Researchers have developed a growing interest in Vitamin D due to its functions beyond calcium metabolism. Methods: This study was undertaken to clarify the relationship between body mass index (BMI), physical activity and levels of Vitamin D, especially in medical students. It was a cross-sectional study conducted in 1st year and 2nd year MBBS students with the age group of 17–22 years, consisting of both sexes and the participants were allocated by random sampling. Vitamin D levels in serum were measured using ELISA method. Students were asked to fill the Questionnaire Short Form - International Physical Activity – (IPAQ – SF) and based on the categorical scoring, physical activity is classified as low, moderate, and high. Pearson’s correlation coefficient was used to find out the correlations between the variables. BMI showed significant negative correlation (r=−0.15, p=0.04) with serum Vitamin D. Results: It was found that mean Vitamin D (49.7±30.50) was higher in BMI<25 (normal weight) which showed statistically significant difference (p=0.04) when compared with BMI 25 to 30 (over weight) (42.6±31.73) and BMI>30 (obese) (34.6±25.16). Conclusion: Physical inactivity and obesity have an adverse effect of Vitamin D. The present study reinforces that screening of population for Vitamin D is mandatory, particularly among people who are overweight and obese.